2002
DOI: 10.1128/aac.46.7.2116-2123.2002
|View full text |Cite
|
Sign up to set email alerts
|

Enzymes Associated with Reductive Activation and Action of Nitazoxanide, Nitrofurans, and Metronidazole in Helicobacter pylori

Abstract: Nitazoxanide (NTZ) is a redox-active nitrothiazolyl-salicylamide prodrug that kills Helicobacter pylori and also many anaerobic bacterial, protozoan, and helminthic species. Here we describe development and use of a spectrophotometric assay, based on nitroreduction of NTZ at 412 nm, to identify H. pylori enzymes responsible for its activation and mode of action. Three enzymes that reduce NTZ were identified: two related NADPH nitroreductases, which also mediate susceptibility to metronidazole (MTZ) (RdxA and F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
172
2
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 158 publications
(180 citation statements)
references
References 35 publications
5
172
2
1
Order By: Relevance
“…However, solid experimental evidence for this hypothesis is missing. Studies in H. pylori suggested that, in contrast to metronidazole, NTZ was largely non-mutagenic (Sisson et al 2002). However, the prescribing information on NTZ (Alinia TM ) states that the drug was genotoxic in one tester strain (TA 100) in the Ames bacterial mutation assay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, solid experimental evidence for this hypothesis is missing. Studies in H. pylori suggested that, in contrast to metronidazole, NTZ was largely non-mutagenic (Sisson et al 2002). However, the prescribing information on NTZ (Alinia TM ) states that the drug was genotoxic in one tester strain (TA 100) in the Ames bacterial mutation assay.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, NTZ exhibits a broad spectrum of activities against a wide variety of enteric bacteria, protozoa, and intestinal and tissue-dwelling helminth parasites, infecting animals and humans (Fox and Saravolatz, 2005 ;Pankuch and Appelbaum, 2006). Against Helicobacter pylori, Giardia intestinalis and Cryptosporidium parvum, the drug has been postulated to act via reduction of its nitro-group by nitroreductases, including pyruvate ferredoxin oxidoreductase (PFOR) (Coombs and Muller, 2002 ;Sisson et al 2002). In terms of veterinary use, the drug is marketed for the treatment of equine myeloencephalitis caused by Sarcocystis neurona (Navigator TM ).…”
mentioning
confidence: 99%
“…The 5-nitroimidazoles, such as metronidazole, are activated only by anaerobic enzyme systems that generate very low redox potentials (Ϫ480 mV), such as pyruvate-ferrodoxin oxidoreductases and hydrogenases (14). However, neither redox potential nor hydrophobicity correlates with the activity of various nitroimidazoles against Trichomonas vaginalis, suggesting a specific protein-ligand interaction (15).…”
Section: Discussionmentioning
confidence: 99%
“…Susceptibility results from the action of one or two related nitroreductases that each mediate conversion of Mtz from harmless prodrug to hydroxylamine, a bactericidal and mutagenic agent; RdxA, which is abundant in essentially all Mtz s clinical isolates; and FrxA, which is present at only very low levels in most isolates (designated type I strains) but at higher levels in others (type II strains) (27,28). RdxA and FrxA differ in substrate specificity (49), but their normal substrates, products, and roles (e.g., whether purely metabolic or protective against reactive nitrogen and oxygen metabolites that are produced in the host response to infection; see reference 40) are not known.…”
mentioning
confidence: 99%